2009
DOI: 10.1021/la804021t
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of DNA Microarrays with Poly(l-glutamic acid) Monolayers on Gold Substrates for SPR Imaging Measurements

Abstract: Robust single-stranded DNA (ssDNA) microarrays are created by attaching amine-modified oligonucleotides to a monolayer of poly-L-glutamic acid (pGlu) that is electrostatically adsorbed onto a chemically modified gold thin film. This surface attachment chemistry methodology is first characterized with a combination of polarization-modulation Fourier transform infrared (PM-FTIR) spectroscopy and surface plasmon resonance (SPR) angle shift measurements. SPR imaging (SPRI) measurements of these ssDNA microarrays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 30 publications
6
83
0
Order By: Relevance
“…SPR imaging techniques have been used to study the sequence-specific adsorption of response regulator proteins to DNA [103,104], bioaffinity interactions in peptide arrays [105], proteins [106], and carbohydrate-protein interactions [107]. A very important feature in SPR imaging is the spatial resolution of the image that is determined by the propagation length of the SP at the interface between the metal and the analyte, which is dependent on the dielectric constant of the metal film, the refractive index of the analyte, and the frequency of the incident light (see Eq.…”
Section: Spr Imaging Techniques For Sensingmentioning
confidence: 99%
“…SPR imaging techniques have been used to study the sequence-specific adsorption of response regulator proteins to DNA [103,104], bioaffinity interactions in peptide arrays [105], proteins [106], and carbohydrate-protein interactions [107]. A very important feature in SPR imaging is the spatial resolution of the image that is determined by the propagation length of the SP at the interface between the metal and the analyte, which is dependent on the dielectric constant of the metal film, the refractive index of the analyte, and the frequency of the incident light (see Eq.…”
Section: Spr Imaging Techniques For Sensingmentioning
confidence: 99%
“…To detect even lower concentrations of biomolecules with SPRI, a number of nanoparticle-based and surface enzyme-based signal amplification schemes have been implemented. 17-25 For example, we have previously shown that the method of RNase H-amplified SPRI can be used to detect ssDNA down to a concentration of 10 fM. 26,27 However, all of our previous studies have been performed with milliliter samples in a circulating flow cell format that creates a steady state concentration gradient from solution to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of chemical attachment and surface enzymatic attachment reactions are used to create single-stranded DNA and RNA (ssDNA and ssRNA respectively) microarrays. 17,29 After array fabrication, the microchannels are flushed out with buffer solution, and then four separate 3 μL target volumes are introduced into the microchambers of the biochip. Real-time SPRI measurements are used to monitor the specific adsorption of ssDNA and two proteins, single stranded DNA binding protein and thrombin, onto the microarray elements from quiescent nanomolar solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Maleimide-functionalized NTA was attached to the gold thin film microarray elements using a SATP strategy shown in Figure 4 that has been described and characterized previously 22 (Figure 4). The SPRI chips also include a thin hydrophobic Sigmacote film on the glass areas surrounding the gold microarray elements to prevent crosstalk during the fabrication process 19 . The NTA-functionalized chips were exposed to an aqueous 40 mM Cu II solution for 15 minutes and then rinsed with nanopure water.…”
Section: Resultsmentioning
confidence: 99%